Association of Work Schedules With Nurse Turnover: A Cross-Sectional National Study - Sung-Heui Bae (Frontiers Media S.A., 2023)
Objective: To examine the relationship of work schedules with nurse turnover across various work settings.Methods: A cross-sectional study design was used with data collected from 17,046 nurses who participated in the 2018 National Sample Survey of Registered Nurses in the U.S. Multivariate logistic regression was used to examine the effects of work hours and overtime on nurse turnover.Results: Longer weekly work hours increased nurse turnover (OR = 1.104, 95% confidence interval [CI] = 1.006-1.023). A non-linear relationship was observed between overtime and turnover. Compared with nurses with no overtime, the turnover for nurses working 1-11 h overtime per week decreased (OR = 0.893, 95% CI = 0.798-0.999). When nurses worked ≥12 h, turnover increased (OR = 1.260, 95% CI = 1.028-1.545). Earning from the primary nursing position decreased turnover among nurses working in hospitals, other inpatient settings, and clinics. Job satisfaction decreased turnover.Conclusion: To prevent nurse turnover, it is important to monitor and regulate nurses' working hours at institutional and government levels. Government support and policy implementations can help prevent turnover.